Dehulled and naked oats in mink and blue fox diets - Koskinen, Nita; Pölönen, Ilpo; Rekilä, Teppo; Valaja, Jarmo (PO, 2005)
Results All mink and blue foxes maintained good health throughout both experiments. Mink In the digestibility trial mean final weights in mink (Figure 1) were equal in all diet groups (1846.7 - 1908.3 g), except the group dehulled oats 15 % where it was lower. In the production trial no statistically significant differences between treatments were found in weight gain (Figure 3). In the latter part of this experiment (November) mink fed 50 % dehulled oats gained even more than did the mink whose diet contained only barley as a cereal source. The differences in skin length, weight and characteristics were small and not significant (Table 3). Blue fox In the digestibility trial mean final weights of blue foxes were equal in all diets (Figure 1, 7355 - 7687 g). Average daily gain of blue foxes varied between 77.4-81.5 g. Final average weights varied from 13.49 to 13.75 kg (Figure 4). The differences in skin length, weight and characteristics were small (Table 4). Only quard hair quality, in the group 8% dehulled oats became better than in other groups. Discussion Somewhat poorer weight gain in mink in the groups of 8 and 16 % dehulled oats did ot confirm the results of digestibility trial, where the difference in digestibility was not seen. The preliminary results of the digestibility trial show that both dehulled and naked oats diets were highly digestible. The difference may originate from looser and softer consistencys of dehulled oats diets. Dehulled oats finer particle size (2 mm) resulted in looser and softer consistency and probably led to feed waste from the wire mesh. The problem arose only with mink because the mink cages did not have feeding trays. In contrast, blue fox fed with the same experimental feed gained similarly to other diets. Van Barneveld et. al (1997) also studied digestibility of naked and dehulled oats in growing pigs and found that both dehulled and naked oats have very high amino acid digestibility. These results indicate that both naked and dehulled oats can promote good weight gain both in mink and blue foxes. Naked oats have been included in commercial young pigs diets with positive growth responses. Dehulled and naked oats have even been found very good feed ingredients for dogs. Amino acid content and profile oats is better than in corn Kempe et al. (2004). Our results, both digestibility data, growth and fur properties show that dehulled and naked oats are suitable ingredients in mink and blue fox diets. Naked oats is a new crop and not yet widely cultivated in Finland. Recent studies have shown that some varieties produce yields as high as common oats (Kangas et al., 2001). Hence, naked and dehulled oats will have a potential as a feed ingredient in fur bearing animal diets. References van Barneveld, R. J., Szarvas, S. R. and Barr, A. R. (1998). The apparent ileal digestibility of amino acids and the digestible energy content of naked oats (Avena sativa cv Bandicoot) fed to growing pigs. Journal of the Science of Food and Agriculture. 76:2, 277-284. Kangas, A., Salo, Y., and Vuorinen, M. 2001. Naked oats strains produce good crops both in amount and quality (in Finnish). MTT/Koetoiminta ja käytäntö. 2001/1:3. Kempe, R., Saastamoinen, M. and Hyyppä, S. (2004). Composition, digestibility and nutritive value of cereals for dogs. Agricultural and Food Science 13: 5-17.